Are Proteinase 3 and Cathepsin C Enzymes Related to Pathogenesis of Periodontitis?. (18th May 2014) - Türkoğlu, Oya; Azarsız, Elif; Emingil, Gülnur; Kütükçüler, Necil; Atilla, Gül
Abstract : Aim . Cathepsin C is the activator of the polymorphonuclear leukocyte-derived proteinase 3, which contributes to inflammatory processes. The aim of the present study was to investigate gingival crevicular fluid (GCF) proteinase 3 and cathepsin C levels in periodontal diseases. Design . Eighteen patients with chronic periodontitis (CP), 20 patients with generalized aggressive periodontitis (G-AgP), 20 patients with gingivitis, and 18 healthy subjects were included in the study. Periodontal parameters including probing depth, clinical attachment level, papilla bleeding index, and plaque index were assessed in all study subjects. GCF proteinase 3 and cathepsin C levels were analyzed by ELISA. Results . GCF proteinase 3 total amount was significantly higher in diseased groups compared to control group, after adjusting age P < 0.05 . No differences were found in GCF cathepsin C levels among the study groups P > 0.05 . Periodontal parameters of sampling sites were positively correlated with GCF proteinase 3 total amounts P < 0.01 but not with cathepsin C total amounts P > 0.05 . Conclusions . Elevated levels of GCF proteinase 3 in CP, G-AgP, and gingivitis might suggest that proteinase 3 plays a role during inflammatory periodontal events in host response. However, cathepsin C in GCF does not seem to have an effect on the pathogenesis of periodontal diseases.